TINJAUAN KRIMINOLOGIS TENTANG KEJAHATAN PENCURIAN KENDARAAN BERMOTOR RODA DUA DI WILAYAH HUKUM POLSEK KOTA SAMARINDA KALIMANTAN TIMUR - Novianti, Rita (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACTAs relations between one community and another occur, various incidents arise, one of which is a legal incident due to the phenomenon of theft of two-wheeled motorized vehicles in the Samarinda city police area becoming a frequent problem, the high number of motorized vehicle theft cases has a significant impact on security and public order and gives rise to material and psychological losses for victims. The existence of this phenomenon can be the basis for selection in this problem. The formulation of this problem is to identify the causal factors that cause motor theft crimes, both internal factors that occur within the perpetrator, lack of education level and an individual's religious morals as one of the things that influence someone to commit a crime (stealing). and a lack of a person's level of piety and faith, this causes the crime of theft to occur. As well as external factors that occur due to the lack of economic conditions to meet daily needs, the environment also has a big influence on the occurrence of theft (especially living in an environment that supports stealing) and global developments which have a positive impact on the country but for individuals it becomes a matter of competition between one individual and another. another. This research method uses empirical juridical research, using primary and secondary materials so that it is analyzed qualitatively and the research in this thesis conducted interviews, namely interviews. By using this research method, it is hoped that we can answer the facts that occurred in the jurisdiction of the Samarinda City Police. From the interview process carried out, it can be concluded that the countermeasures carried out by the police involve preventive and repressive strategies. Preventive strategies aim to reduce the opportunity for perpetrators to commit crimes, while repression is carried out by enforcing the law against perpetrators who are caught. From the results of this research, it is hoped that it can provide a significant contribution in understanding the phenomenon of two-wheeled motor vehicle theft crimes in the jurisdiction of the Samarinda City Police. By understanding what factors influence the occurrence of these crimes, we can tackle this theft problem effectively. Keywords: Criminological, Motor Vehicle Thieft.